Nanoclays for Lipase Immobilization: Biocatalyst Characterization and Activity in Polyester Synthesis - Hale Öztürk; Eric Pollet; Vincent Phalip; Yüksel Güvenilir; Luc Avérous (Polymers, 2016)
The immobilization of Candida antarctica lipase B (CALB) was performed by physical adsorption on both neat and organo-modified forms of sepiolite and montmorillonite. The influence of different parameters, e.g., solvent, enzyme loading, cross-linking, and type of clay support, on immobilization efficiency and catalyst hydrolytic activity has been investigated. The highest hydrolytic activities were obtained for CALB immobilized on organo-modified clay minerals, highlighting the beneficial effect of organo-modification. The esterification activity of these CALB/organoclay catalysts was also tested in the ring-opening polymerization of ε-caprolactone. The polymerization kinetics observed for clay-immobilized catalysts confirmed that CALB adsorbed on organo-modified montmorillonite (CALB/MMTMOD) was the highest-performing catalytic system.